The Black Book of Quantum Chromodynamics a Primer for the LHC Era - Campbell, John (Oxford University Press, 2018)
The LHC (Large Hadron Collider) will serve as the energy frontier for high-energy physics for the next 20 years. The highlight of the LHC running so far has been the discovery of the Higgs boson, but the LHC programme has also consisted of the measurement of a myriad of other Standard Model processes, as well as searches for Beyond-the-Standard-Model physics, and the discrimination between possible new physics signatures and their Standard Model backgrounds. Essentially all of the physics processes at the LHC depend on quantum chromodynamics, or QCD, in the production, or in the decay stages, or in both. This book has been written as an advanced primer for physics at the LHC, providing a pedagogical guide for the calculation of QCD and Standard Model predictions, using state-of-the-art theoretical frameworks. The predictions are compared to both the legacy data from the Tevatron, as well as the data obtained thus far from the LHC, with intuitive connections between data and theory supplied where possible. The book is written at a level suitable for advanced graduate students, and thus could be used in a graduate course, but is also intended for every physicist interested in physics at the LHC.